1989
DOI: 10.1159/000185771
|View full text |Cite
|
Sign up to set email alerts
|

Use of Permcath (Quinton) Catheter in Uraemic Patients in Whom the Creation of Conventional Vascular Access for Haemodialysis Is Difficult

Abstract: During the last 4 years, the Permcath Quinton double-lumen silicone catheter was inserted into the internal jugular vein of 57 uraemic patients with difficulty for creating conventional vascular access for haemodialysis. In 4 patients, with definitive contraindication of conventional vascular access, this catheter still permits haemodialysis after a duration of 8–25 months. In 25 further patients with terminal uraemia, but poor vein system, it allowed the maturation of an arteriovenous fistula after 2–14 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…Interestingly, such lack of difference was evident in both patients with and without evident causes of inflammation. Serwanska-Swietek et al (30) were able to detect the presence of a DNA fragment of approximately 790 bp in length in all of the whole blood samples randomly selected from a group of 50 hemodialysis patients without signs of active infection but did not correlate this presence with markers of inflammation. With regard to other diseases, Sleigh et al have shown that 16S rDNA PCR resulted positive in 14.8% of critically ill patients with negative blood cultures and was approximately twice as sensitive as blood culture in detecting bacteraemia in patients who previously received antibiotics (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, such lack of difference was evident in both patients with and without evident causes of inflammation. Serwanska-Swietek et al (30) were able to detect the presence of a DNA fragment of approximately 790 bp in length in all of the whole blood samples randomly selected from a group of 50 hemodialysis patients without signs of active infection but did not correlate this presence with markers of inflammation. With regard to other diseases, Sleigh et al have shown that 16S rDNA PCR resulted positive in 14.8% of critically ill patients with negative blood cultures and was approximately twice as sensitive as blood culture in detecting bacteraemia in patients who previously received antibiotics (17).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of the present study results by future studies may raise the question of how to manage bacterial DNA detected in the whole blood of hemodialysis patients. To the best of our knowledge, there are limited data on this issue (9,30). In general, the presence of bacterial DNA in the whole blood is considered an expression of bacteraemia and suggests that the patient be considered for antibiotic therapy (16 -19,31).…”
Section: Discussionmentioning
confidence: 99%
“…One option is to continue systemic antibiotics alone, in an attempt to salvage the infected catheter. This approach should be discouraged, because bacteremia recurs in approximately 75% of patients once the course of antibiotics has been completed (98,135,138,146,147). In a recent prospective study, the risk for treatment failure was five-fold higher in patients with attempted catheter salvage, as compared with patients in whom the infected catheter was removed (140).…”
Section: Diagnosis and Treatment Of Catheter-related Bacteremiamentioning
confidence: 99%
“…Several different catheters are available world-wide. The two most popular types used in France in the 1990s were the Permcath cuffed double catheter [2,3,5,[19][20][21], and the TwinCath noncuffed catheter described first by Canaud et al [4], then modified by Tesio et al [6] as a cuffed version. These two devices represent two different approaches to avoid dysfunction and infectious catheterrelated problems.…”
Section: Introductionmentioning
confidence: 99%